2020
DOI: 10.1101/2020.02.17.952903
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular mechanism of evolution and human infection with the novel coronavirus (2019-nCoV)

Abstract: AbstractSince December, 2019, an outbreak of pneumonia caused by the new coronavirus (2019-nCoV) has hit the city of Wuhan in the Hubei Province. With the continuous development of the epidemic, it has become a national public health crisis and calls for urgent antiviral treatments or vaccines. The spike protein on the coronavirus envelope is critical for host cell infection and virus vitality. Previous studies showed that 2019-nCoV is highly homologous to human SARS-CoV and at… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 35 publications
2
24
0
5
Order By: Relevance
“…[64][65][66][67] Despite 2019-nCoV and SARS-CoV share ACE2 receptor on host cells, which are found in salivary gland and tongue tissues, [23][24][25]29,53 2019-nCoV is likely more infectious than SARS-CoV possibly due to lower RBD-ACE2 binding free energy and more flexible RBD of 2019-nCoV than that of SARS-CoV. 70 Compared with SARS-CoV, a furin-like cleavage site is peculiar in the S protein of 2019-nCoV, which could theoretically be cleaved by furin expressed in tongue tissues. 33,34 For saliva droplets as transmission routine in coronavirus infection, a retrospective cohort study of SARS-CoV transmission reported that students who were in the same cubicle with the SARS patient contracted SARS-CoV, telling us that proximity to SARS patients increases chances of SARS-CoV infection.…”
Section: Infectious Saliva Dropletsmentioning
confidence: 99%
“…[64][65][66][67] Despite 2019-nCoV and SARS-CoV share ACE2 receptor on host cells, which are found in salivary gland and tongue tissues, [23][24][25]29,53 2019-nCoV is likely more infectious than SARS-CoV possibly due to lower RBD-ACE2 binding free energy and more flexible RBD of 2019-nCoV than that of SARS-CoV. 70 Compared with SARS-CoV, a furin-like cleavage site is peculiar in the S protein of 2019-nCoV, which could theoretically be cleaved by furin expressed in tongue tissues. 33,34 For saliva droplets as transmission routine in coronavirus infection, a retrospective cohort study of SARS-CoV transmission reported that students who were in the same cubicle with the SARS patient contracted SARS-CoV, telling us that proximity to SARS patients increases chances of SARS-CoV infection.…”
Section: Infectious Saliva Dropletsmentioning
confidence: 99%
“…By investigating the variations in the residue changes across the entire S protein sequence or all the regions of lower variability (Figure 2a and Table S1), the S2 subunit exhibited the lowest sequence variability (residue range; 816-1141; Figure 1b and 2c). Moreover, previous studies have identified that the active site region for this S protein is located in the RBD domain which interacts with the host cell receptor, ACE2 [18,20,26,38,39,40,42,44]. Comparing the variability of the RBD domain (which is targeted for drug designing approaches) and S2 subunit domains, the RBD domain was shown to contain more mutations in its region compared to the HR1, CH and CD domains Figure 2b, 2c, and Table S1, S2, S3, S4).…”
Section: Variability In the Spike Glycoproteinmentioning
confidence: 99%
“…Several studies have aimed to define the mechanism of binding of SARS-CoV-2 to the host cell receptor [38]. Molecular dynamics simulations of the spike(RBD)-ACE2 complex over 10 ns indicated that RBD-ACE2 binding free energy for SARS-CoV-2 is better than the SARS-CoV [39]. Similarly, other studies have shown that the SARS-CoV-2 S protein has a better binding affinity to ACE2 at two different "up" angles of the RBD than SARS-CoV [40].…”
Section: Introductionmentioning
confidence: 99%
“…The coronavirus SARS-CoV-2 (previously known as nCoV -19) has been 4 associated with the recent epidemic of acute respiratory distress syndrome 5 [9], [2]. Recent studies have suggested that the virus binds to the ACE2 6 receptor on the surface of the host cell using the spike protein and explored 7 the binary interaction of these two partners [4,12,28]. In this work, we 8 focused our analysis on the interface residues to get insight into four main 9 subjects: (1) The architecture of the interface of the spike protein and 10 whether its evolution in many isolates supports an increase in affinity 11 toward the ACE2 receptor; (2) How the affinity of SARS-COV-2-RBD and 12 SARS-CoV-RBD toward different ACE2 homologous proteins from different 13 species is dictated by a divergent interface sequences (3); A comparison of 14 the interaction hotspots between SARS-CoV and SARS-CoV-2; and finally, 15 (4) whether any of the studied ACE2 variants may show a different binding 16 property compared to the reference allele.…”
mentioning
confidence: 99%